The Hindu-Muslim problem: a cooperative approach - Engineer, Asghar Ali (Islam and Christian-Muslim relations, 1990)
This document, widely circulated in India, argues that the Hindu‐Muslim problem has political, socio‐economic and religious aspects. Here the emphasis is on the Muslim component. It was political hostility which assumed the form of religious hostility. The rise of religio‐cultural separatism and Islamization must be viewed not simply as a facet of ‘Muslim fanaticism’ but rather as a sociological process which resulted from the political struggles between the élites of the two communities and of a heightened political consciousness. But the identity of the Muslims of India remains. Their ‘Muslimness’ cannot completely submerge their ‘Indianness’. Whereas Hindus are asked to show respect for the Muslim minority's cultural‐religious sensibilities, Muslims should opt for a progressive and not a regressive indentity.